Penerapan Digital Accounting dan Dampaknya terhadap Kinerja Usaha UMKM di Kecamatan Sukarame Bandar Lampung (International Forum of Researchers and Lecturers, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in driving Indonesia's economy forward, acting as the cornerstone for inclusive and sustainable economic development. However, these enterprises face a formidable challenge in expanding their operations. While effective financial management is paramount for success, many MSME practitioners lack awareness regarding the significance of meticulous and accurate financial record-keeping. To tackle this challenge, information technology, particularly digital accounting, presents promising solutions capable of enhancing the efficiency and precision of financial reporting. This research delves into the implementation of digital accounting among MSMEs in the Sukarame district, Bandar Lampung, aiming to scrutinize its impact on business performance. Employing a qualitative approach, the study seeks to grasp the perceptions, experiences, and everyday practices of MSME practitioners concerning the utilization of digital accounting applications. Through this inquiry, it aspires to cultivate a more comprehensive and contextual understanding of the ramifications of digital accounting adoption on Lampung's MSME sector, offering pertinent insights for policy formulation and the advancement of digital accounting practices across Indonesia. Ultimately, this study aims to contribute to the body of knowledge surrounding MSMEs' integration of digital accounting, promoting sustainable growth and economic inclusivity in Indonesia.